Pengaruh Komunikasi, Motivasi, Dan Lingkungan Kerja Terhadap Kinerja Karyawan : (Studi Kasus Pada PT. Daehan Global) - Desvitriani Nurakza; Muhammad Syaifulloh; Nur Khojin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to examine the influence of Communication, Motivation and Work Environment on Employee Performance at PT. Daehan Global. The population of this research focuses on all employees in the Cutting Department of PT. Daehan Global, namely 86 employees with the sample type, namely saturated samples. Data was collected using a questionnaire method. The data analysis method in this research uses multiple linear regression analysis, coefficient of determination, and hypothesis testing t test and F test. The results of this research show that: Communication partially has a positive and significant effect on the performance of PT employees. Daehan Global. Motivation partially has a positive and significant effect on the performance of PT employees. Daehan Global. The work environment partially has a positive and significant effect on the performance of PT employees. Daehan Global. Communication (X1), motivation (X2) and work environment (X3) simultaneously / together have a positive and significant effect on the performance of PT employees. Daehan Global. The contribution of the independent variables communication (X1), motivation (X2) and work environment (X3) to the dependent variable employee performance (Y) is 0,532 or 53,2%, the contribution of variable X provides sufficient explanation for variable Y. Meanwhile the remaining 46,8% is another factor not discussed in this study.